Barriers affecting export performance of Nigerian SMEs in the leather industry - Junaidu, Abubakar Sambo (2013)
Despite the large amount of research that has been carried out to investigate the factors that affect export performance, very little research has been conducted for specific industries operating in developing countries like Nigeria. This is the case even though findings from past studies seem to indicate that export barriers are not only country but also industry specific. The specific roles of moderating and mediating variables have also being seemingly neglected in past research. This present work therefore, is a study of the factors that affect export performance of SMEs in the Nigerian leather industry. In so doing, this research evaluates the relationship between nine categories of export barriers grouped into tangible resources, intangible resources and facilitating factors on the one hand and firm export performance on the other. Based on the contingency paradigm and the resource-based view,this study posits that (1) knowledge resources barriers, (2) communication resources barriers,(3) exogenous barriers, (4) export support structure barriers, (5) image resources barriers, (6) operational resources barriers, (7) financial resources barriers, (8) marketing resources barriers and (9) human resources barriers are all strongly related to firm export performance. The study also hypothesizes that firm size moderates the relationship between tangible resources barriers and export performance and that entrepreneurial orientation moderates the relationship between tangible as well as intangible resources and export performance. Perception of export difficulty is hypothesized to mediate the relationship between intangible resources barriers and export performance. The survey type of data collection whereby self-dministered questionnaires were distributed to respondents was used for data collection. Questionnaires were mostly directly distributed and collected by trained enumerators. Data for the study was collected in Nigeria and the target sample was drawn from (1) Manufacturers Association of Nigeria (MAN), (2) the Nigerian Industrial Directory and (3) the Nigerian Exporters directory. In addition, the lists of members of the local tannery councils in the study areas were used to obtain the names of SMEs to include in the sample. Given that this research is centred on firm level activities and their impacts, the unit of analysis is at the firm level. All in 623 questionnaires were distributed and 458 were collected over a period of nine weeks for a response rate of about 74% and out of the 458, 449 usable questionnaires were obtained finally 117 questionaires were used for the analysis on exporting SMEs. Descriptive statistics were used to analyse the relative severity of export barriers and multiple regression analysis was used for hypotheses testing. Findings from the data analysis provide support for all the hypothesized relationships thus suggesting support for the theoretical model of the study.